phan tich da thuc thanh nhan tu : \(a^6+a^4+a^2b^2+b^4-b^6\)
phan tich da thuc thanh nhan tu
a, x^2+x-6
b,x^4+4
a)\(x^2+x-6\)
\(=x^2-2x+3x-6\)
\(=\left(x^2-2x\right)+\left(3x-6\right)\)
\(=x\left(x-2\right)+3\left(x-2\right)\)
\(=\left(x-2\right)\left(x+3\right)\)
a) x2 + x - 6
= x2 - 2x + 3x - 6
= (x2 - 2x) + (3x - 6)
= x(x - 2) + 3(x - 2)
= (x + 3)(x - 2)
b) x4 + 4
= x4 + 4x2 + 4 - 4x2
= (x4 + 4x2 + 4) - 4x2
= (x + 2)2 - 4x2
= (x + 2 - 2x)(x + 2 +2x)
phan tich da thuc:(a^2+b^2-c^2)^2-4a^2b^2 thanh nhan tu
\(\left(a^2+b^2-c^2\right)^2-4a^2b^2\)
\(=\left(a^2+b^2-c^2\right)^2-\left(2ab\right)^2\)
\(=\left[\left(a+b\right)^2-c^2\right]\left[\left(a-b\right)^2+c^2\right]\)
=(a+b+c)(a+b-c)(a-b+c)(a-b-c)
Phan tich da thuc thanh nhan tu
a(a+2b)^3-b(2a+b)^3
=a(a+2b)^3-[-b(a+2b)^3]
=(a+2b)^3(a+b)
phan tich da thuc thanh nhan tu
4a^2b^2-(a^2+b^2-c^2)^2
Phan tich da thuc sau thanh nhan tu:
a) \(a\left(b+c\right)^2+b\left(c+a\right)^2+c\left(a+b\right)^2\)
b)\(a^4+b^4+c^4-2a^2b^2-2a^2c^2-2c^2b^2\)
1 phan tich da thuc thanh nhan tu
a) 4x^2 - 49
b) a^2 -2a -b^2 -2b
a/ \(4x^2-49=\left(2x\right)^2-7^2=\left(2x-7\right)\left(2x+7\right)\)
b/ \(a^2-2a-b^2-2b=\left(a^2-2a+1\right)-\left(b^2+2b+1\right)=\left(a-1\right)^2-\left(b+1\right)^2\)
\(=\left(a-1-b-1\right)\left(a-1+b+1\right)=\left(a-b-2\right)\left(a+b\right)\)
phan tich da thuc thanh nhan tu
A=x^6-2x^5-4x^4+6x^3+4x^2-2x-1
phan tich da thuc thanh nhan tu a. x^3+x+2
b, x^4+5x^3+10x-4
\(x^3+x+2=\left(x^3+1\right)+\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x+1\right)+\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2-x+1+1\right)\)
\(=\left(x+1\right)\left(x^2-x+2\right)\)
\(b,x^4+5x^3+10x-4=\left(x^4-4\right)+\left(5x^3-10x\right)\)\(=\left(x^2+2\right)\left(x^2-2\right)+5x\left(x^2+2\right)\)
\(=\left(x^2+2\right)\left(x^2-2+5x\right)\)
Phan tich da thuc thanh nhan tu
a) \(x^2+7x+6\)
b) \(x^4+2008x^2+2007x+2008\)
a, x^2 + 7x + 6
= x^2 + x + 6x + 6
= x(x + 1) + 6(x + 1)
= (x + 6)(x + 1)
\(x^2+7x+6\)
\(=x^2+x+6x+6\)
\(=x\left(x+1\right)+6\left(x+1\right)\)
\(=\left(x+6\right)\left(x+1\right)\)
\(a,x^2+7x+6\)
\(=x^2+x+6x+6\)
\(=x\left(x+1\right)+6\left(x+1\right)\)
\(=\left(x+1\right)\left(x+6\right)\)
\(b,x^4+2008x^2+2007x+2008\)
\(=x^4-x+2008x^2+2008x+2008\)
\(=x\left(x^3-1\right)+2008\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2008\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2008\right)\)